ABO-incompatible kidney transplantation enabled by Non-Antigen-Specific immunoadsorption - Morath, Christian; Becker, Luis Eduardo; Leo, Albrecht; Beimler, Jörg; Klein, Katrin; Seckinger, Jörg; Kihm, Lars Philipp; Schemmer, Peter; Macher-Göppinger, Stephan; Opelz, Gerhard; Süsal, Caner; Zeier, Martin; et al. (Transplantation, 2012)
Background. ABO-incompatible kidney transplantation performed after desensitization with antigen-specific immunoadsorption (IA) results in good outcomes. However, a unique single-use IA device is required, which creates high costs. Methods. From August 2005 to August 2010, 19 patients were desensitized for ABO-incompatible living donor kidney transplantation. Six patients treated with a single-use antigen-specific IA device and 12 patients treated with a reusable non-antigen-specific IA device were analyzed. Results. Six patients who received antigen-specific IA had a median of 5 IA treatments and 12 patients with non-antigen-specific IA had a median of 6 IA treatments preoperatively. Median average titer drop in Coombs technique was 1.2 in antigen-specific IA and 1.7 in non-antigen-specific IA. In two patients with antigen-specific IA and four patients with non-antigen-specific IA, additional plasmapheresis treatments were necessary for recipient desensitization. Despite six treatments with antigen-specific IA and 12 plasmapheresis treatments, one patient with a starting isoagglutinin titer of 1:1024 (Coombs) could not be transplanted. The 18-month graft survival rate for the 17 ABO-incompatible living donor kidney transplants was 100%. One male recipient who was desensitized with antigen-specific IA died 44 months after transplantation from sudden cardiac death with a serum creatinine of 1.2 mg/dL. At last follow-up, a median of 13 months after transplantation, median serum creatinine for 16 patients was 1.5 mg/dL, median glomerular filtration rate as estimated by the modification of diet in renal disease formula 54 mL/min/1.73 m2, and median urinary protein-to-creatinine ratio 0.1, with no differences between treatments. Conclusions. A reusable non-antigen-specific IA device allows high number of treatments at reasonable cost, and at the same time might deplete human leukocyte antigen-alloantibodies.